Murder in the margins - Loudon, Margaret (Loudon, Margaret. Open book mysteries., 2020)
Hit with a bad case of writer's block, American gothic author Penelope Parish heads to England where she, while working in a bookstore, gets embroiled in a murder investigation that leads to new friendships and new tricks to help her finish her novel.